1989
DOI: 10.1143/jjap.28.l2213
|View full text |Cite
|
Sign up to set email alerts
|

Josephson Effect in Wide Superconducting Bridges Made by Epitaxial Ba2YCu3Ox Thin Films on YSZ/Si(100)

Abstract: Using the silicon substrates patterned with the trench, the superconducting microbridge junction has been fabricated in as-grown Ba2YCu3O x thin films by rf magnetron sputtering. The microbridge junctions with constrictions as small as submicron dimensions were obtained. These microbridge junctions behaved as Josephson junctions and microwave-induced steps were observed. The observed characteristics seem to be consistent with those expected for a homogeneous wide superco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1990
1990
1993
1993

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The regions that do not trap the magnetic field correspond also to the position for which the sample height changes by more than 0.25 p.m. The decoupling of regions of the superconducting film deposited on cleaved surfaces separated by more than 0.25 p,m can be caused by a complete lack of connection between these regions since the film is only 0.3 p,m Myoren et al (7) observed that for 0.5 p,m thick films evaporated onto a 3 p,m deep trench, the isolation between devices separated by the trench was almost complete. In our case, the largest cleavage steps are 0.5 p,m and, using the SEM, we observed that the superconducting film is continuous across these steps.…”
mentioning
confidence: 99%
“…The regions that do not trap the magnetic field correspond also to the position for which the sample height changes by more than 0.25 p.m. The decoupling of regions of the superconducting film deposited on cleaved surfaces separated by more than 0.25 p,m can be caused by a complete lack of connection between these regions since the film is only 0.3 p,m Myoren et al (7) observed that for 0.5 p,m thick films evaporated onto a 3 p,m deep trench, the isolation between devices separated by the trench was almost complete. In our case, the largest cleavage steps are 0.5 p,m and, using the SEM, we observed that the superconducting film is continuous across these steps.…”
mentioning
confidence: 99%
“…This effect has been studied extensively regarding conventional superconductors [2,3]. Only few observations have been reported so far for microbridges structured in films of high-Tc oxide superconductors with sufficiently small dimensions [4][5][6]. In the theory of AL thermally activated flux motion (TAFM) [7,8] was not taken into account.…”
mentioning
confidence: 99%